Market efficiency in the emerging securitized real estate markets - Felix Schindler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper tests the random walk hypothesis and market efficiency for twelve emerging as well as for four developed securitized real estate markets from 1992 to 2009. Random walk properties of equity prices influence return dynamics, and market efficiency is often considered an essential criterion in the assessment of the functionality of markets and the asset pricing process, which is of significant relevance for emerging markets in particular. The analysis is based on autocorrelation tests as well as both single variance and multiple variance ratio tests. Furthermore, non-parametric runs tests are conducted. Empirical evidence shows that the efficient market hypothesis in its weak form is not rejected by any statistical test for seven of the twelve analyzed emerging securitized real estate markets. This result is surprising since all four developed securitized real estate stock markets analyzed in this study do not follow a random walk. The results are confirmed by the analysis of excess returns following from technical trading rules.
Keywords: G12; G14; G15; 330; Securitized real estate markets; market efficiency; random walk hypothesis; variance ratio tests; runs test; trading strategies; Immobilienmarkt; Securitization; Hypothek; Markteffizienz; Random Walk; Statistischer Test; Schätzung; Aufstrebende Märkte; Schwellenländer